Effect of Mg2+ ions co-doping on luminescence and defects formation processes in Gd3(Ga,Al)5O12:Ce single crystals - Babin, V.; Boháček, Pavel; Grigorjeva, Larisa; Kucera, Miroslav; Nikl, M.; Zazubovich, S.; Zolotarjovs, Aleksejs (Elsevier B.V., 2017)
Photo- and radioluminescence and thermally stimulated luminescence characteristics of Ce³⁺ - doped and Ce³⁺, Mg²⁺ co-doped Gd3(Ga,Al)5O12 (GAGG) single crystals of similar composition are investigated in the 9–500 K temperature range. The Ce³⁺ - related luminescence spectra and the photoluminescence decay kinetics in these crystals are found to be similar. Under photoexcitation in the Ce³⁺ - and Gd³⁺ - related absorption bands, no prominent rise of the photoluminescence intensity in time is observed neither in GAGG:Ce,Mg nor in GAGG:Ce crystals. The afterglow is strongly reduced in GAGG:Ce,Mg as compared to GAGG:Ce, and the afterglow decay kinetics is much faster. Co-doping with Mg²⁺ results in a drastic decrease of the thermally stimulated luminescence (TSL) intensity in the whole investigated temperature range and in the appearance of a new complex Mg²⁺ - related TSL glow curve peak around 285 K. After irradiation in the Ce³⁺ - related 3.6 eV absorption band, the TSL intensity in GAGG:Ce,Mg is found to be comparable with that in the GAGG:Ce epitaxial film of similar composition. The Mg²⁺ - induced changes in the concentration, origin and structure of the crystal lattice defects and their influence on the scintillation characteristics of GAGG:Ce,Mg are discussed.
The work was supported by the Institutional Research Funding IUT02-26 of the Estonian Ministry of Education and Research and the project 16-15569S of the Czech Science Foundation.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; Luminescence; Multicomponent garnets; Single crystals; Ce3+; Mg2+; Scintillators